International Intercomparison of In Situ Chlorophyll-a Measurements for Data Quality Assurance of the Swedish Monitoring Program - Kratzer, Susanne; Harvey, E. Therese; Canuti, Elisabetta (Frontiers in Remote Sensing, 2022)
Chlorophyll-a measured in situ is used for the validation of satellite images. Previous intercomparisons have shown that there can be 25-75% differences between in situ laboratories. In order to shed light on these differences, we arranged a dedicated Chlorophyll-a international intercomparisons with 8 participating laboratories during 1-2 July 2021. We performed 2 dedicated transects through Bråviken bay (NW Baltic proper) and sampled 4 stations in each transect along a Chlorophyll-a gradient. We took 3 surface replicates per laboratory and per station, i.e. 24 samples per laboratory. The samples were filtered through Whatman GF/F filters, and filters were frozen in liquid nitrogen, and distributed in dry ice to all laboratories together with Chlorophyll-a standards. The concentration of the standards was determined by High Performance Liquid Chromatography (HPLC). The results between labs compared well. The Mean Normalized Bias (MNB) of the standard measurements ranged between -23% and +19% for all laboratories, and -7% to +19% for the Baltic Sea laboratories compared to HPLC. The MNB of the 2 Bråviken transects ranged between -23 to +17% for all laboratories (compared to the median of all spectrophotometric and fluorometric measurements), and between -2 to +17% for the Baltic Sea laboratories. On average, the Chlorophyll-a concentrations measured by the fluorometric method were about 13% higher than measured by spectrophotometry. The highest uncertainties seem to be caused by variable storage and extraction methods, and are not fully captured in this intercomparison. This is demonstrated by analyzing historical comparisons revealing very large uncertainties (root mean square difference (RMSD) up to 109% and a bias up to 68% due to inappropriate extraction and storage methods. Our recommendation is to flash-freeze samples in liquid nitrogen and to store them at -80ºC. After storage they should be measured at room temperature within 6-24 h. Last but not least we would like to point out that the uncertainties in measuring Chlorophyll-a by satellite are now within a similar range as for in situ data as shown here by comparing the in situ results from this study with published remote sensing results from the literature.